Evaluation of Water Facilities to Support Operations at Kuala Tungkal Ferry Port Based on KM No. 52 of 2004 - Santoso, Santoso; Utami, Fisca Dian; Arkani, Hari; Agustina, Hera; Hidaya, Judge Junizar (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
The availability of Fenders at the Kuala Tungkal Ro-Ro Ferry Port is lacking and many are damaged, resulting in greater impacts to the pier, if it continues to occur, it will damage the pier building. The researcher's goal is to determine the condition of the water facilities and analyze the need for fenders and bolders as water facilities at the Kuala Tungkal Ro-Ro Ferry Port. The current condition of the Bolder is damaged and rusty, making it dangerous for ships to moor. Analysis of existing problems, based on the Bambang Triatmodjo Transportation Planning Book in 2009. The results of this study are: 1.) There are no fenders in good condition, all fenders have been damaged and torn for ships operating at the Kuala Tungkal Ro-Ro Ferry Port, the current condition of the fenders is torn, hanging and loose, and there is still a shortage of 1 fender 2.) The current condition of the Bolder Tip is corroded so that it can endanger ships that will moor. Water facilities at the Kuala Tungkal Ro-Ro Ferry Port require rejuvenation of the Bolder iron in order to provide safe, comfortable, and optimal services, then the Fender requires rejuvenation or installation according to the dimensions of the operating ship, so that impacts on the pier can be withstood by the fender and the addition of one fender at the end of the port dolphin.